2023
DOI: 10.3390/app132111618
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Demand Forecasting and Optimal Scheduling of the Oxygen Gas Systems in Iron- and Steel-Making Enterprises

Zhen Cheng,
Peikun Zhang,
Li Wang

Abstract: Due to the imbalance between the supply and demand of oxygen, the oxygen systems of iron- and steel-making enterprises in China have problems with high oxygen emissions and high pressure in the pipelines, resulting in the energy consumption of oxygen production being high. To reduce the energy consumption of oxygen systems, this study took a large-scale iron- and steel-making enterprise as a case study and developed a two-stage forecasting and scheduling model. The novel aspect and progressiveness of this work… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Experiments showed that this method outperformed other energy consumption prediction models. Zhen Cheng et al [21] proposed a back propagation neural network based on genetic algorithm optimization for oxygen demand prediction model of iron and steel enterprises, and experimentally proved that the prediction accuracy of the model was better than that of the ARIMA model. Shenglong Jiang et al [22] proposed a hybrid model integrating multivariate linear regression and Gaussian process regression for the prediction of oxygen consumption in the converter steel training process, and verified the accuracy of the model with real data.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments showed that this method outperformed other energy consumption prediction models. Zhen Cheng et al [21] proposed a back propagation neural network based on genetic algorithm optimization for oxygen demand prediction model of iron and steel enterprises, and experimentally proved that the prediction accuracy of the model was better than that of the ARIMA model. Shenglong Jiang et al [22] proposed a hybrid model integrating multivariate linear regression and Gaussian process regression for the prediction of oxygen consumption in the converter steel training process, and verified the accuracy of the model with real data.…”
Section: Introductionmentioning
confidence: 99%